The forgetfulness of balls and bins. Issue 2 (23rd February 2012) - Perkins, Will
Abstract We find the asymptotic total variation distance between two distributions on configurations of m balls in n labeled bins: in the first, each ball is placed in a bin uniformly at random; in the second, k balls are planted in an arbitrary but fixed arrangement and the remaining m ‐ k balls placed uniformly at random. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2012